Effect of salt addition on the thermal behavior of proteins of bovine meat from Argentina - Pighin, Darío Gabriel; Sancho, Ana Maria; Gonzalez, Claudia Beatriz (Elsevier, 2019)
Research was undertaken to investigate how the addition of sodium chloride (NaCl) and/or sodium tripolyphosphate (TPP) to sous vide cooked meat pieces produces an increase in water holding capacity (WHC). Semitendinosus muscles were injected to obtain tissue final concentrations of 0.70% NaCl, 0.25% TPP, 0.70% NaCl + 0.25% TPP, and 1.20% NaCl + 0.25% TPP. SDS-PAGE analysis showed increased protein solubilization in those treatments which included NaCl. Thermal analysis of whole muscles and isolated myofibrils showed the destabilizing effect of NaCl and a global stabilizing effect of TPP. Both salts together induced a destabilizing global effect, where TPP assisted NaCl in breaking the meat structure. It is suggested that the WHC increments are related to conformational changes in myofibrillar proteins and to the weakening of myofibrillar structure by the removal of myofibrillar proteins.